Vascular endothelial growth factor promotes neurite maturation in primary CNS neuronal cultures - Khaibullina, Alfia A.; Rosenstein, Jeffrey M.; Krum, Janette M. (Brain research. Developmental brain research, 2004)
Recent studies have demonstrated that vascular endothelial growth factor (VEGF) and its receptor VEGFR2 (flk-1) are expressed by neurons during development and following hypoxic–ischemic events. Moreover, fetal CNS tissue explants exposed to exogenous VEGF exhibit increased neuronal Map-2 expression, suggesting that VEGF could have an effect on neuronal maturation. To determine whether this effect is of a direct nature, we examined the expression of Map-2 in the presence of VEGF in primary CNS neuronal cultures. After 3 days in culture, a statistically significant dose-dependent increase in the length of Map-2(+) processes was observed, with the peak occurring at 10 ng/ml of VEGF. Immunohistochemical analysis of the cultures demonstrated the presence of VEGFR2 after VEGF treatment, as well as the expression of the VEGF receptor VEGFR1 (flt-1). Treatment of the cultures with antisense oligonucleotides against VEGFR2, but not against VEGFR1, abolished the effect of VEGF on the length of Map-2(+) processes. RT-PCR analyses of Map-2 and VEGFR1 indicated that mRNAs of these two genes are upregulated in the presence of VEGF. The addition of wortmannin, an inhibitor of PI3K/Akt signal-transduction pathway, to the media did not affect the VEGF-dependent increase in Map-2(+) length. In contrast PD98059, which inhibits the MAPK pathway, partially abolished this effect of VEGF. These experiments suggest that VEGF has a direct effect on neuronal growth and maturation under normoxic conditions during CNS development, which is mediated by the VEGFR2 receptor via the MAPK pathway.